Transforming Waste into Wealth: Implementation of Qanun Concerning Waste Management in Lhokseumawe City, Aceh - Velayati, Sajidah; Fithra, Herman; Hafni, Nur; Fazil, Muhammad; Sohheng, Nipon (Master Program of Sociology, Universitas Malikussaleh,, 2023)
Waste management has transcended from a mere environmental concern to a pivotal economic opportunity, particularly in urban landscapes. The Government of Lhokseumawe City has issued the Qanun Number 9 of 2015 concerning waste management, a cornerstone in this paradigm shift. This study analyzes the implementation of the Qanun for economic values in Lhokseumawe City and the obstacles faced in its execution. The research adopts a qualitative approach using data collection techniques such as observation, interviews, and documentation. The findings reveal that the full implementation of Qanun Number 9 is hindered by budget constraints at the Environmental Agency (DLH) of Lhokseumawe City and challenging social environmental conditions, which make waste management difficult to control. Even though DLH has set appropriate waste management targets, obstacles cannot be avoided, including ineffective socialization, apathy towards cleanliness, and difficulties faced by micro, small and medium enterprises (MSMEs) in obtaining raw materials for plastic waste. Meanwhile, positive supporting factors were found, including the persistent efforts of officers in carrying out outreach activities, increased public awareness of the importance of cleanliness, and support from village officials in waste management outreach activities carried out by DLH.